Perancangan Program Turbo Vision untuk Peningkatan Profesionalisme Guru Dahsyat Bagi Proses Pembelajaran Peserta Didik Unggul di Sekolah Menengah Atas/Kejuruan - Asep Rohmandar (Publikasi Indonesia, 2022)
In the design of the identification and analysis of the Turbo Vision variable dimension program in improving the professionalism of powerful teachers for the learning process of superior students in senior / vocational high schools (Kanji Tindak at SMA / SMK Telkom Bandung) has provided a unique and new object variable dimension that needs further development. Where this is in accordance with the characteristics of the turbo vision program. Although this new turbo vision program was tested by the author in the process of social research, because the theory actually comes from computer programming. From the results of identification, observation and sharp analysis carried out that turbo vision is in line with objective programming which produces a new program system. If the new program is generalized, it appears in the character and nature of a relatively permanent (repetitive) system in the form of system characteristic objects in the form of aspects and dimensions of Input / Input, Process / Process, Output / Output, Impact / Impact (IPOI / MPKD) in a system that is running (operating) or that will be operated, including in the organization of education units.